Macbeth - Shakespeare, William, 1564-1616. (Hauppauge, N.Y. : Barron's, 2002)
Presents the original text of Shakespeare's play side by side with a modern version, with discussion questions, role-playing scenarios, and other study activities.
"Original Shakespearean text, with a modern line-for-line translation."
Includes bibliographical references (p. 245-249).
Keywords: Macbeth, -- King of Scotland, -- active 11th century -- Juvenile drama; Shakespeare, William, -- 1564-1616.; Regicides -- Juvenile drama; Children's plays, English; Plays; English literature -- History and criticism; Scotland -- Juvenile drama